2011
DOI: 10.1007/s13595-011-0048-4
|View full text |Cite
|
Sign up to set email alerts
|

Autumn fertilization of Quercus ilex ssp. ballota (Desf.) Samp. nursery seedlings: effects on morpho-physiology and field performance

Abstract: & Background The Holm oak (Quercus ilex ssp. ballota [Desf.] Samp.) is an evergreen tree widely distributed in the western Mediterranean Basin. Forest restoration programs using this species have enjoyed only limited success, and knowledge concerning the effect of fertilization on plant quality and post-transplantation response is sparse. & Methods We assessed the effect of autumn fertilization using different doses of nitrogen, phosphorus, and potassium (70.0 mg N, 30.5 mg P and 58.1 mg K during the growing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 31 publications
5
30
0
2
Order By: Relevance
“…Franco (van den Driessche 1985, Birchler et al 2001, Eucalyptus globulus Labill. (Fernández et al 2007), and Quercus ilex L. (Oliet et al 2011, Andivia et al 2011, 2012. Fall fertilization at the nursery can build nutrient reserves in seedlings, especially in the foliage (van den Driessche 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Franco (van den Driessche 1985, Birchler et al 2001, Eucalyptus globulus Labill. (Fernández et al 2007), and Quercus ilex L. (Oliet et al 2011, Andivia et al 2011, 2012. Fall fertilization at the nursery can build nutrient reserves in seedlings, especially in the foliage (van den Driessche 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of fertilization and frost hardiness has focused on evergreen tree species, such as Pinus resinosa (Islam et al 2009), Picea abies (Fløistad and Kohmann 2004), Picea mariana (Bigras et al 1996), Pseudotsuga menziesii (Birchler et al 2001), and Quercus ilex (Andivia et al 2011(Andivia et al , 2012, with little attention paid to deciduous tree species. In most forest nurseries, frost hardiness is commonly evaluated using freeze-induced electrolyte leakage (FIEL) (Bigras and Colombo 2001) because, compared to the whole-plant freeze test, FIEL yields a more rapid, sensitive, and objective predictor of differences in tissue frost hardiness (Burr et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, nitrogen (N) can affect the cold and drought tolerance, yet there is no clear consensus on the magnitude or direction of its effect. Low tissue N concentration may hinder either cold or drought hardening [32]. Proper available nitrogen in soils enhanced the growth of plants and lowered the adverse effect on growth caused by water stress [33].…”
Section: Resultsmentioning
confidence: 99%
“…Mineral nutrients (N, P, K) were only determined in leaves because Andivia et al (2011) reported that differences in nutrient concentration and content of plants given different N fertilization treatments were much greater in leaves than in other tissues. To obtain leaf samples sufficiently large for nutrient analysis, three groups per dose of N were formed.…”
Section: Morphological and Nutritional Statusmentioning
confidence: 99%
“…N fertilization can improve photosynthetic rate, root growth, and water-use efficiency (Fernández et al 2006;Lambers et al 1990). A previous study with Holm oak has reported that N has a greater effect than P or K on morphological and nutritional status and improvement of seedling frost tolerance (Andivia et al 2011). However, the latter assay only studied two levels of N fertilization and the nursery fertilization programs for this species require additional refinement ).…”
Section: Introductionmentioning
confidence: 99%